(untitled) (Principles and Practice of Clinical Research, 2022)
Background: Preterm Infants in the Neonatal Intensive Care Unit (NICU) undergo many procedures that cause pain and stress, which require the use of large amounts of analgesics and sedatives. Drugs, although important, can have adverse effects, are not always available, due to their high cost, and can increase the length of stay at the NICU. As a result, the adoption of non-pharmacological measures to control stress has increased in this population, despite little evidence of their efficacy. The main objective of this study will be to identify which non-pharmacological measures are more effective to control pain and stress in preterm infants.Methods: Systematic review and network meta-analysis protocol of clinical trials searched in MedLine databases via PubMed, Latin American and Caribbean Literature in Health Sciences (LILACS), Excerpta Medica dataBASE (Embase), The Cochrane Central Register of Controlled Trials (CENTRAL), and Physiotherapy Evidence Database (PEDro). Descriptors to be used: premature, pain management, therapeutic touch, facilitated folding, sucking behavior, kangaroo method, analgesics, sedatives, pain, stress, weight gain, facial expression, crying, sleep, and wakefulness. The detailed study protocol was registered in the International Prospective Registry of Systematic Reviews (PROSPERO - CRD42020196891).Discussion: Elimination of pain in premature infants in NICU may be difficult, but it should be a daily goal, as well as the stabilization of other clinical variables. Non-pharmacological measures can be helpful to reduce the amount and intensity of pain. Knowledge of the efficacy of non-pharmacological measures to control pain and stress in NICU premature infants is essential. It may reduce complications, the length of stay at the NICU and minimize the use of analgesics.